Making an impact through research. (13th May 2017) - Fitzpatrick, Julie
Abstract : Julie Fitzpatrick grew up in rural Ayrshire, surrounded by dogs, cats, ponies and other animals, with aspirations of working in mixed practice. She now heads the Moredun Group in Edinburgh